Numerical and Finite Element Analysis of RC Beams Strengthened With a Novel Technique Using External Plates and Rebars - Sina Soltanpour; Morteza Sheikhi (Advances in Civil Engineering)
The necessity to reinforce structural members is an inevitable consideration for various reasons. Given the considerable expenses associated with laboratory studies, numerical research can significantly contribute to achieving superior results alongside traditional laboratory methods. The present study aims to numerically investigate the behavior of reinforced concrete (RC) beams that have been strengthened by applying a novel technique with the use of external plates and rebars. A finite element model was created for analyzing the performance of the reinforced beams, and its accuracy was confirmed by comparing it to data obtained from earlier investigations. A parametric analysis was carried out to examine the impact of different parameters, including different concrete compressive strengths, rebar diameters, distances from the beam soffit, and rebar lengths. Results demonstrate significant improvements in load-carrying capacity by up to 51% and energy absorption by up to 40% across all configurations. The numerical analysis of the strengthened beam, including rigid connection assumptions for external reinforcement, yielded an ultimate load of 19.9 kN, closely matching FEM results. Two behavioral modes (governed by axial and bending interactions) were analytically derived, and an interaction diagram optimized the cracking coefficient to 0.5, demonstrating how external rebars enhance bending resistance through axial load introduction. These improvements indicate possible uses in the repair and enhancement of current RC structures, providing a cost-efficient and effective method for prolonging the lifespan of infrastructure.